Does foreign aid reduce energy and carbon intensities in developing countries? - Bettina Kretschmer; Michael Hübler; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2010)
Advanced OECD countries are widely held responsible to contain global carbon emissions by providing financial and technical support to developing economies, where emissions are increasing most rapidly. It is open to question, however, whether more generous official development assistance would help fight climate change effectively. Empirical evidence on the effects of foreign aid on energy and emission intensities in recipient countries hardly exists. We contribute to closing this gap by considering energy use and carbon emissions as dependent climate-related variables, and the volume and structure of aid as possible determinants. In particular, we assess the impact of aid that donors classify to be specifically related to energy issues. In addition to OLS estimations, we perform dynamic panel GMM and LSDVC (corrected least squared dummy variables) estimations. We find that aid tends to be effective in reducing the energy intensity of GDP in recipient countries. All the same, the carbon intensity of energy use is hardly affected. Scaling up aid efforts would thus be insufficient to fight climate change beyond improving energy efficiency.
Keywords: F35; Q41; Q55; 330; Energy intensity; CO2 emissions; foreign aid; developing countries; Entwicklungshilfe; OECD-Staaten-seitig; Klimaschutz; Energiesparen; Kohlendioxid; Luftreinhaltung; Wirkungsanalyse; Entwicklungsländer